Textile reinforced mortars for masonry structures - Kariou, Florentia (2020)
Unreinforced masonry (URM) is a common engineering practice in different types of construction, e.g., structural bearing walls and infill panels, bridge arches and cultural heritage buildings. Recent catastrophic events such as the earthquakes in L’Aquila (2009), Tohoku, Japan (2011), Christchurch (2011), Northern Italy (2012), and Central Italy (2016–2017) have tragically pointed out the need for restoration and strengthening of existing masonry structures. Masonry structures are also prone to ageing related structural deterioration, accelerated by the effect of adverse environmental actions, e.g., high speed winds and heavy rainfalls.